2020
DOI: 10.2147/cmar.s257441
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circ-ZNF609 Accelerates the Radioresistance of Prostate Cancer Cells by Promoting the Glycolytic Metabolism Through miR-501-3p/HK2 Axis</p>

Abstract: Background: The development of radioresistance remains the obstacle for prostate cancer (PCa) treatment. Here, we explored the role and potential mechanism of circular RNA zinc finger protein 609 (circ-ZNF609) in the radioresistance of PCa cells. Materials and Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the expression of circ-ZNF609, microRNA-501-3p (miR-501-3p) and hexokinase 2 (HK2) messenger RNA (mRNA). The viability, apoptosis, metastasis and radioresistance of PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 30 publications
1
29
1
Order By: Relevance
“…Following sanger sequencing, RNase R treatment and RT-qPCR analysis, the six DECs were validated and their decreased expression in GC tissues was confirmed. Previous studies have revealed that hsa_circ_0000615 acts as miRNA sponge to exert different roles in different solid tumors [ 37 40 ]; for example, hsa_circ_0000615 upregulates Sp1 expression by adsorbing miR-150-5p, and thereby promoting the proliferation and metastasis of nasopharyngeal cancer cells [ 38 ]. However, until now studies about the effect of hsa_circ_0000615 and the other five DECs on GC have been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Following sanger sequencing, RNase R treatment and RT-qPCR analysis, the six DECs were validated and their decreased expression in GC tissues was confirmed. Previous studies have revealed that hsa_circ_0000615 acts as miRNA sponge to exert different roles in different solid tumors [ 37 40 ]; for example, hsa_circ_0000615 upregulates Sp1 expression by adsorbing miR-150-5p, and thereby promoting the proliferation and metastasis of nasopharyngeal cancer cells [ 38 ]. However, until now studies about the effect of hsa_circ_0000615 and the other five DECs on GC have been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“… 33 For example, in prostate cancer, circular RNA could promote tumor progression and radioresistance by upregulating glycolysis. 34 Therefore, it will be a promising treatment to reverse the metabolic state of tumor with drugs. Studies have shown that sulforaphane can prevent the occurrence of prostate cancer by inhibiting glycolysis and fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Recently, some circRNAs have been shown to be transferred by exosomes and thus involve in human carcinogenesis and radioresistance development. 12 , 13 A previous report uncovered that circ_0067835 could inhibit cell proliferation and metastasis in endometrial carcinoma. 14 Importantly, circ_0067835 contributed to CRC development by regulating miR-1236-3p/homeobox B7 (HOXB7) axis.…”
Section: Introductionmentioning
confidence: 99%